Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
For more than a decade, growth in Germany has been subdued and uneven. This paper introduces the stylized facts pertaining to the strength in exports, the weakness in domestic demand, and the surge in the current account. It discusses the adjustment undertaken in the private sector and its impact on exports and domestic demand, followed by fiscal and monetary policies and their macroeconomic impact. Finally, structural impediments accelerating capital exports and the rising current account surplus are outlined.